Memahami Ajaran Paus Pius XII Tentang Devosi Kepada Hati Kudus Yesus Dan Implementasinya Bagi Hidup Kaum Beriman - Restu Ningsih Waruwu; Alexius Poto Obe; Evimawati Harefa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
In general, the Catholic Church is based on two spiritual activities, namely the official liturgy and devotions. The difference between the two is more about legality and the place where the activity is carried out in a place that has been officially and sacredly determined, namely the church. Whereas devotion is more flexible and can be carried out anywhere, such as; shrines, churches, or in homes. Devotion is very close to the expression of love for God’s love and including his Son Jesus Christ, the world’s savior who atones for human sins. In imitating the Most Sacred Heart of Jesus, there are various opportunities that the Church has provided, so that people can live and reflect and ask themselves, why do we have to be devoted? How to obtain the fruits of devotion? People can learn devotion from the life of a Only Begotten Son of God, who was willing to suffer and be crucified. One of them is Jesus Christ who has a Most Sacred Heart. The church is aware of the importance of devotion to the Sacred Heart of Jesus, although many believers still do not understand the value of this devotion, so that from this understanding and motivations emerge in understanding devotion to the Sacred Heart of Jesus, such as devotional practices centered on objects of statues. The people themselves still do not fully understand the devotion to the Sacred Heart of Jesus. So form here the author finds the most basic things that can help people in increasing their piety to Jesus Christ in understanding the teachings of devotion to the Sacred Heart of Jesus according to Pope Pius XII. So by understanding the teachings of Pope Pius XII about devotion. People can implement and understand more about devotion to the Sacred Heart of Jesus that devotion to the Sacred Heart of Jesus is not a burden but a godliness of life and can know His heart which is full of mercy.